University rankings as KOS: Theoretical considerations - Chaves Guimarães, José Augusto [UNESP] (Universidade Federal da Paraíba, 2020)
Considering the knowledge organization systems as a core issue in the knowledge organization field, this paper focuses on international university rankings as a new incarnation of KOS through an analysis of their classificatory nature. For this, four important international university rankings are analyzed: THE, Shanghai, Leiden, and QS in terms of their notation, facets, citation order, editions, and updating. The results confirm their classificatory nature as essentially faceted systems whose structure is derived from specific contextual slants and whose dynamic updating process leads to a constant remodeling of the structure and the weight of the facets.
Os rankings universitários como sistemas de organização do conhecimento: Considerações teóricas
Keywords: Classificatory structures; Knowledge organization systems; University rankings